The Human Side of Humanitarian Work: Well-Being and Performance Among Aid Workers in Egypt - Kenawy, Mai Osama (AUC Knowledge Fountain, 2026)
Well-being and productivity are widely recognized as central to the work performance of humanitarian aid workers. Despite increasing attention to staff well-being, performance within the humanitarian sector in Egypt remains stagnant or, in some cases, declining. This study examines why expanded well-being initiatives have not yielded sustained performance improvements by examining how actors' external roles, organizational factors, and individual factors affect humanitarian workers’ well-being and work performance. A mixed-methods approach was adopted, combining ten in-depth interviews with humanitarian workers from international organizations, INGOs, and local NGOs, as well as a survey of eighty workers operating in the same context. The findings demonstrate that well-being plays a critical role in humanitarian performance, particularly given the work's purpose-driven nature. When organizational factors such as bureaucratic structures and donor-driven priorities are supportive, workers show higher motivation, ethical engagement, and sustainable, human-centered performance; when these factors are unsupportive, performance becomes increasingly mechanical and challenging to sustain. Addressing these organizational influences is essential for developing effective well-being initiatives.